Mampukah Usaha Rumah Tangga Penggalian Garam Tambang Industri di Indonesia Mencapai Produksi Optimal? - Adila, Rani; Budiasih, Budiasih (Seminar Nasional Official Statistics, 2023)
Production of industrial mine salt in Indonesia is still not sufficient for national needs, forcing Indonesia to import it. In fact, the potential of the region and its resources to become a salt producer is enormous. This is allegedly due to inefficiencies in the production process. It is known that one of the salts that generally has industrial salt levels of Sodium Chloride (NaCl) is mine salt. Therefore, this study examines whether there is technical inefficiency and its determinants of industrial salt mining household businesses in Indonesia. The data used is raw data from the Annual Survey of Industrial Material Quarrying and Construction with the GALIAN-URT questionnaire in Indonesia in 2022. Cobb-Douglas Stochastic Frontier Analysis (SFA) is used to measure technical inefficiency. The results of this study indicate that the length of time a business operates has a positive effect on technical efficiency. The average technical efficiency obtained is 0.66 which means that production is not optimal. Variations in inefficiency between businesses are dominated by variables that cannot be controlled by business owners.